GCN5L1/BLOS1 Links Acetylation, Organelle Remodeling, and Metabolism. Issue 5 (May 2018) - Scott, Iain; Wang, Lingdi; Wu, Kaiyuan; Thapa, Dharendra; Sack, Michael N.
Abstract : General control of amino acid synthesis 5 (GCN5) like-1 (GCN5L1) was identified as a novel gene with sequence homology to the histone acetyltransferase Gcn5. Subsequent protein-interaction studies identified GCN5L1 as a subunit of the multiprotein lysosome biogenesis complex, resulting in an alternative designation as biogenesis of lysosome-related organelle complex 1 subunit 1 (BLOS1 or BLOC1S1). Despite the distinct nomenclatures, GCN5L1/BLOS1 has been shown to play crucial roles in mitochondria, endosomes, lysosomes, and synaptic vesicle precursors (SVPs). GCN5L1/BLOS1 controls mitochondrial protein acetylation, modulates metabolic pathways, and orchestrates retrograde mitochondria-to-nucleus signaling. It also contributes to endosome–lysosome and vesicle trafficking and to endolysosomal function. Here we discuss the intracellular roles of GCN5L1/BLOS1 in the hope of linking mitochondria-centric effects to cytosolic vesicle biology. Highlights: GCN5L1, BLOS1, and BLOC1S1 are alternative names of the same gene product implicated in several distinct mitochondrial and cytosolic pathways. This protein was initially designated GCN5L1 due to its sequence homology to the nuclear acetyltransferase GCN5. GCN5L1 does not contain an acetyltransferase catalytic domain but may promote protein acetylation in the presence of acetyl-CoA generation pathways or contribute to acetylation as an acetyl-CoA-binding protein. The depletion of GCN5L1 has dose-dependent effects in modulating protein acetylation and retrograde signaling with profound effects on mitochondrial turnover and biogenesis. The first functional target of GCN5L1 has been identified as the mitochondria-associated kinesin Kif1Bα-binding protein (KBP). BLOS1/BLOC1S1 deficiency disrupts endosome–lysosome and synaptic vesicle precursor trafficking. BLOS1/BLOC1S1 disrupts endolysosome and lysosome functioning.